Factors Associated With Opioid Use in Presurgical Knee, Hip, and Spine Osteoarthritis Patients. Issue 9 (3rd August 2019) - Power, J. Denise; Perruccio, Anthony V.; Gandhi, Rajiv; Veillette, Christian; Davey, J. Roderick; Lewis, Stephen J.; Syed, Khalid; Mahomed, Nizar N.; Rampersaud, Y. Raja
Abstract : Objective: To evaluate rates of prescription opioid use among patients with presurgical knee, hip, and spine osteoarthritis (OA) and associations between use and sociodemographic and health status characteristics. Methods: Participants were patients with presurgical, end‐stage OA of the knee (n = 77), hip (n = 459), and spine (n = 168). Data were collected on current use of opioids and other pain medications, as well as measures of sociodemographic and health status variables and depression and pain (0–10 numeric rating scale). Rates of opioid use were calculated by sex, age, and surgical site. Multivariable logistic regression was used to examine associations between opioid use (sometimes/daily versus never) and other study variables. Results: The mean age of participants was 65.6 years; 55.5% were women, 15% of patients reported "sometimes" using opioids, and 15% reported "daily use." Use of opioids was highest among patients with spine OA (40%) and similar among patients with knee and hip OA (28% and 30%, respectively). Younger women (ages <65 years) reported the greatest use of opioids overall, particularly among patients with spine OA. From multivariable logistic regression, greater likelihood of opioid use was significantly associated with spine OA (versus knee OA), obesity, being a current or former smoker, higher symptomatic joint count, greater depressive symptoms, greater pain, and current use of other prescription pain medication. Conclusion: Nearly one‐third of patients with presurgical OA used prescription opioid medication. Given the questionable efficacy of opioids in OA and risk of adverse effects, higher opioid use among younger individuals and those with depressive symptoms is of concern and warrants further investigation.